Batch and continuous processes food manufacturing case studies - Legh, Richard; Video Education Australasia (Bendigo, Vic : Video Education Australia, 2005)
Case studies of Brunetti's Cafe in Melbourne and Pura Milk in this program show us the difference between batch processing and continuous processing in food production
Director , editor , Christine Rogers ; camera , Zane Loritt, Richard Leign ; sound, Wayne Martin , Alexy Gusdimenro ; graphics , Lansun Tan ; Executive producer ; Marie McAuliffe
Voice over : Simone Marshall
Keywords: Food industry and trade -- case studies; Food industry and trade -- Production control